Effects of a native avian predator (weka; Gallirallus australis) and colony density on breeding success of a burrow-nesting seabird (tītī; Ardenna grisea) - Joanna K. Carpenter; David Fletcher; James Arbuckle; Morgan Coleman; Becky Goodsell; Andrew Gormley; Aurora Metzger; Trent Moss; Kate H. Orwin; Darren Scott; Luke Sutton; Theo D. W. Thompson; et al. (PLoS ONE, 2026)
As island ecosystems are restored, native predators are recovering and re-establishing interactions with their prey. However, compared with widely-publicised impacts of invasive predators, little is known about the dynamics and stability of native predator-prey dynamics on islands. Prey species such as seabirds may still be vulnerable to population decline, as even native predation can become unsustainable at a population-level when combined with other threats. Large seabird colonies may buffer against native predation by diluting its per-capita impact, but this will depend on the functional response of native predators to prey densities. Here, we test the impact of a predatory native rail (weka, Gallirallus australis ) on breeding success of a burrow-nesting seabird (tītī/muttonbird/sooty shearwater, Ardenna grisea ) that nests in dense colonies on the Rakiura Tītī Islands, southern New Zealand. We used burrowscopes and trail cameras to assess tītī breeding success ( N = 126 nests) at three sites with weka, and two sites without. We also tested how tītī burrow density (a proxy for colony density) influenced breeding success. Tītī breeding success (probability of an egg hatching and then fledging) varied across sites, ranging from 0.39 to 0.88. Model predictions indicated that weka had a negligible effect on tītī breeding success overall, with breeding success increasing with increasing tītī burrow density, although both relationships had considerable uncertainty. Trail camera data showed weka activity was primarily diurnal, and that weka activity at monitored burrows did not increase during the period nests are most vulnerable (mid-January until late-February). We suggest that weka predation on tītī may be inversely density dependent, and that large colonies absorb the impact of predation. However, if tītī populations decline in the future due to other factors (e.g., climate change, harvest), the impact of weka on breeding success may increase, resulting in accelerated, localized tītī population declines .